The Effect of Providing Disaster Safety Education With Animated Video Media on The Level of Knowledge of Earthquake Disaster Preparedness at SDN 1 Kadipiro : Pengaruh Pemberian Pendidikan Aman Bencana Dengan Media Video Animasi Terhadap Tingkat Pengetahuan Kesiapsiagaan Bencana Gempa Bumi di SDN 1 Kadipiro - Maghriza, Irna Ari; Susana, Sarka Ade; Maryana (Poltekkes Kemenkes Yogyakarta, 2023)
An earthquake is defined as an event in which energy is released from the earth's interior, characterized by the rupture of rock layers in the earth's crust. Earthquakes rank third after tsunamis and landslides with a prevalence rate of 16%. Lack of awareness about disaster preparedness knowledge is one of the factors that cause many victims of earthquakes, especially in children who are included in vulnerable groups. There are many media used in delivering messages, including animated video media and poster media. This study aims to determine the effect of providing disaster safety education with animated video media on the level of knowledge of earthquake disaster preparedness at SD N 1 Kadipiro. Type of research quasi experimental design with pretest and posttest control group design pattern. This research was conducted in February-April 2023. The research subjects were 106 students consisting of IV and V classes. Hypothesis testing was analyzed using Wilcoxon and Mann Whitney. There is an effect of providing disaster safety education with animated videos. There is a difference in knowledge between pretest and posttest both on animated video media) and poster media (p value = 0.000). There is a significant difference from the provision of disaster safety education as evidenced by the average difference in knowledge between the intervention group and the control group obtained Sig (p value) which is 0.000 (p value <0.05). The conclusion of this research is animated video media can have a significant effect on increasing student knowledge about earthquake disaster preparedness. Gempa bumi didefinisikan sebagai suatu peristiwa di mana energi dilepaskan dari bagian dalam bumi yang ditandai dengan pecahnya lapisan batuan di kerak bumi. Gempa bumi menduduki urutan ketiga setelah tsunami dan longsor dengan tingkat prevalensi 16%. Kurangnya kesadaran tentang pengetahuan kesiapsiagaan dalam menghadapi bencana menjadi salah satu faktor penyebab banyaknya korban akibat gempa bumi, khususnya pada anak-anak dimana termasuk dalam kelompok rentan. Media yang digunakan dalam menyampaikan pesan ada banyak, antara lain media video animasi dan media poster. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian pendidikan aman bencana dengan media video animasi terhadap tingkat pengetahuan kesiapsiagaan bencana gempa bumi di SD N 1 Kadipiro. Jenis penelitian quasi experimental design dengan pola pretest and posttest control group design. Penelitian ini dilaksanakan pada Februari-April 2023. Subjek penelitian adalah 106 siswa terdiri dari kelas IV dan V. Uji hipotesis dianalisis menggunakan Wilcoxon dan Mann Whitney. Ada pengaruh dari pemberian pendidikan aman bencana dengan video animasi. Ada perbedaan pengetahuan antara pretest dan posttest baik pada media video animasi) maupun media poster (p value = 0,000). Ada perbedaan yang bermakna dari pemberian pendidikan aman bencana dibuktikkan dengan selisih rata-rata pengetahuan antara kelompok intervensi dan kelompok kontrol didapatkan Sig (p value) yaitu 0,000 (p value <0,05). Kesipulan dari penelitian adalah media video animasi dapat memberikan pengaruh yang bermakna terhadap peningkatan pengetahuan siswa mengenai kesiapsiagaan bencana gempa bumi.